Habitat protection planning for Indo‐Pacific humpback dolphins (Sousa chinensis) in deteriorating environments: Knowledge gaps and recommendations for action - Huang, Shiang‐Lin; Wang, Xianyan; Wu, Haiping; Peng, Chongwei; Jefferson, Thomas A. (Aquatic conservation, 2022)
In Chinese and South‐east Asian waters, the coastal and estuarine environments are important habitats for the Indo‐Pacific humpback dolphin (Sousa chinensis). Coastal and estuarine maritime engineering (CEME), including land reclamation, embankment or shoreline armouring, harbour construction and marine farming, permanently changes coastal environments and threatens the long‐term persistence of marine biota and ecosystems. Such impacts on humpback dolphin viability, however, are rarely discussed. Likely core habitat of the humpback dolphin was extrapolated based on present understanding of habitat characteristics, which is much narrower than present data describing the species’ range. Some uninvestigated habitats near densely populated landscapes may be prone to intense CEME impacts. CEME impacts compromise humpback dolphin survival through habitat loss, population fragmentation, alteration of ecological regimes and deterioration of ecosystem functionality. A 30% loss of core habitat can catastrophically reduce the population viability of this species. The best strategy to avoid CEME impacts on humpback dolphin viability is to adopt a conservative planning regime from the outset. To inform habitat protection planning, current and past habitat configuration and habitat characteristics of the humpback dolphin can be clarified by systematically designed surveys, local ecological knowledge investigation, long‐term satellite remote‐sensing data and species distribution modelling exercises. Sound habitat protection planning includes mapping hierarchical marine protected area (MPA) networks using spatial planning algorithms and carefully examining CEME impacts from an ecosystem perspective. To prevent inappropriate CEME planning, the inclusion of citizen science, local community participation, marine environmental education and effective information delivery is proposed. Questions relating to the proposed areas of habitat loss, the extent of environmental change and the status of population–habitat viability under the scenario of CEME impacts are proposed in order to examine and re‐examine the environmental impacts of any CEME project.